Pulmonary arterial intimal sarcoma with retrograde extension: Report of a case and review of literature - Pradeep Vaideeswar; Raji Pillai (Wolters Kluwer Medknow Publications, 2013)
Most of the pulmonary arterial sarcomas arise from multi-potential mesenchymal intimal cells and are designated as intimal sarcomas. These tumors grow in the direction of blood flow into peripheral arteries producing clinical features mimicking pulmonary thromboembolism. Retrograde extension is rare. We report one such case of intimal sarcoma that had a retrograde extension into the right ventricular outflow tract, and review such a presentation in the last ten years.